2017
DOI: 10.1038/boneres.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the miR-146a-Smad4 axis impairs osteogenesis of bone mesenchymal stem cells under inflammation

Abstract: Osteoporosis is a common disease that affects patient quality of life, especially among the elderly population. Although inflammation contributes significantly to osteoporosis, the underlying mechanism is unclear. In this study, we found that tumor necrosis factor (TNF)-α, an inflammatory environment mimic, inhibits osteogenesis of bone mesenchymal stem cells (BMSCs), induces miR-146a and decreases Smad4. Moreover, overexpression of miR-146a inhibited the osteogenic ability of BMSCs, whereas blocking miR-146a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…Of note, we did not detect major differences of in vitro generated osteoclasts or osteoblasts, which contrast some published reports (Kuang et al, 2017). However, these data were primarily obtained upon manipulation of wt osteoblasts with antagomirs or miR‐146a agonists, while our analyses were done ex vivo with osteoblasts of wt and miR‐146a‐deficient mice, possibly explaining the difference outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Of note, we did not detect major differences of in vitro generated osteoclasts or osteoblasts, which contrast some published reports (Kuang et al, 2017). However, these data were primarily obtained upon manipulation of wt osteoblasts with antagomirs or miR‐146a agonists, while our analyses were done ex vivo with osteoblasts of wt and miR‐146a‐deficient mice, possibly explaining the difference outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…D). To support this statistical analysis, we analyzed another public microRNA array data set (GS74299) , investigating the inverse relationship of Smad4 to miR‐146a expression . miR‐146a was significantly increased in osteoporetic bones compared to healthy ones (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, miR-146a is reportedly involved in high-glucose-induced endothelial inflammation, which suggests that it may be a novel therapeutic target for diabetic vascular disease ( 25 ). Overexpression of miR-146a inhibits osteogenesis by MSCs ( 32 ). In this study, AGEs-BSA had the opposite effects on miR-146a expression in VSMCs and MSCs, possibly explaining its opposite effects on osteogenesis of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential anti-inflammatory effect of miR-146a has widely been reports by the previous studies, Wei et.al reported that, miR-146a inhibits osteoblast proliferation and differentiation that results in the development of osteoporosis ( 32 ). On the other hand, the “off-target” or undesirable side effects such as osteoporosis and Vitamin D deficiency, maybe a major obstacle for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation